2019
DOI: 10.3126/jcmsn.v15i1.20753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollutants on Peak Expiratory Flow Rate of Public Bus Drivers in Bhaktapur, Nepal

Abstract: Background: Rapid increase in number of vehicles in Kathmandu valley over past decade and never ending road expansion projects has aggravated air pollution. People involved in transportation jobs for long duration like bus drivers, conductors are more vulnerable to ill effects of air pollutants. The purpose of the present study was to assess lung function of public bus drivers exposed to outdoor air pollution by means of PEFR. Methods: Fifty healthy, non smoking bus drivers were selected randomly from bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…It was observed that the exposed subjects, had a significantly lower PEFR when compared with the control (p<0.05). This result is in accordance with a study by Karki et al;2019.Again it was noticed that the female control mean values were significantly higher than the female exposed when compared (control=61.57% while exposed=48.33%). More also the female exposed mean values were statistically lower than the male exposed when compared and also across their various ages with the younger adults having higher significant values while the older adults had lower values, and significant differences were not found between the exposed and control males and between the exposed males and females across their age groups.…”
Section: Resultssupporting
confidence: 92%
“…It was observed that the exposed subjects, had a significantly lower PEFR when compared with the control (p<0.05). This result is in accordance with a study by Karki et al;2019.Again it was noticed that the female control mean values were significantly higher than the female exposed when compared (control=61.57% while exposed=48.33%). More also the female exposed mean values were statistically lower than the male exposed when compared and also across their various ages with the younger adults having higher significant values while the older adults had lower values, and significant differences were not found between the exposed and control males and between the exposed males and females across their age groups.…”
Section: Resultssupporting
confidence: 92%
“…Several studies, for example have reported a substantial increase in the prevalence of the respiratory illness among workers of different occupations with apparent positive association with air pollution and occupational exposure [27,[40][41][42][43][44][45].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Son preference in Hindu society promotes more extreme forms of socio-cultural discrimination, cultural values, norms, and attitudes including feticide or infanticide of females (Karki, 1992). As a son is very highly prioritized, valued and daughter is treated as supportive role for sons continue the family name, continue their lineage, transfer of parental properties inherently in lineage system, can perform funeral rituals are and expected to provide support in old age.…”
Section: Introductionmentioning
confidence: 99%
“…As a son is very highly prioritized, valued and daughter is treated as supportive role for sons continue the family name, continue their lineage, transfer of parental properties inherently in lineage system, can perform funeral rituals are and expected to provide support in old age. This patrilineal social structure discourages women from practicing contraception until they have a son (Karki, 1992). If the women conceive the first child a son then she will never thought to conceive another child whether it is son or daughter.…”
Section: Introductionmentioning
confidence: 99%